Quality of education in UiTM Kedah: Bachelor of Administrative Science students’ perspectives / Mohd Firdaus Yusoff and Mohd Firdaus Osman - Yusoff, Mohd Firdaus; Osman, Mohd Firdaus (2010)
The purpose of this study is to analyze the quality of education focus on students’ performance (CGPA) in UiTM Kedah from the Bachelor of Administrative Science students’ perspectives based on the requirement of ISO 9001: 2000 and quality objective in UiTM Kedah . Among the factors that contribute to the quality of education in higher education are facilities, lecturers and student readiness and this study aimed to find out the relationship between the three factors with the quality of education (CGPA). The population of the study is all the students from Bachelor of Administrative Science in UiTM Kedah except part one, two and three student due to still new and not familiar with lecturers and infrastructure provided. The total of 163 students will be represented as the sample size of the study from the all number of populations (census). The research will be taken place one semester from January 2010 until April 2010.